Kijang sebagai simbol dalam rekaan logo Bank Negara Malaysia / Mohd Helmi Mohd Isa - Mohd Helmi , Mohd Isa (2020)
The main purpose of this research was to identify the symbol of barking deer used in the design logo of Bank Negara Malaysia from the aspects of significant and the elements of art usage that are in it. In this study, the authors selected Bank Negara Malaysia as a sample of the organizations to study the symbol of barking deer designed by the famous sculptor Abdul Wahab. This research covers aspects of understanding and significant of the barking deer and the use of elements of art. In addition, there were also interviews with academicians on the design, arts and the Malay studies to get their views and perceptions of the barking deer symbol on the logo. The result of this research is to analyze the meaning of the use of the actual barking deer symbol in the logo design.